Study of Concentration of Added Colors to Juice of Black Cherry and Juice of Barberry on Display in Shop in the City of Tehran - T Faramarzi; A Kamkar; E Pirhadi; T Kaffashi; A Dastbaze; A Najjarian; S Vahedi; MM Soltan Dallal; V Mahdavi (Tehran University of Medical Sciences, 2008)
Background and Aim: Foodstuffs additives are a general term for materials that are added to the foodstuffs in order to increase durability and to improve the appearance, composition, taste and food nutritional value. Colors are classified in this group and are added to foodstuffs in order to increase their attraction. The aim of this survey was to analyze status of added colors to the juice of black cherry and juice of barberry which are produced in Tehran City, capital of Iran.Materials and Methods: Three haundred thirty six samples of dried sweets were randomly collected and analyzed from different areas of Tehran. First, the samples were de-colored by Clorhidric Acid, and then were analyzed after refining by Thin Layer Chromatography (T.L.C) method.Results: Eighty nine percent from the total samples contained colors. Among chromatic samples, 62 samples (18.5%) out the total samples, contained artificial, non-edible colors and 237 samples (70.5%) from the total samples contained artificial and edible colors (for Industrial Producers) and 37 samples (11%), contained natural colors. Carmoisine color was detected more than added colors in juice of black cherry and juice of barberry.Conclusion: Low costs, stability, Ph and similarity of artificial dyes with natural dyes motivate the producers for high utilization of these dyes without considering their possible hazards and/or their edible quality aspects.